THE POTENTIAL OF Heterotrigona itama BEE BREAD IN INHIBITING THE GROWTH OF PATHOGENIC BACTERIA - Suwanti, Tihani Nur Amalina; Arung, Enos Tangke (Universitas Gorontalo, 2026)
Bacterial infections remain a major problem for Indonesians. Bacterial resistance caused by inappropriate antibiotic use is a major factor in the prevalence of bacterial infections in the community. Therefore, the use of natural ingredients is needed as an alternative to natural antibiotics. One natural ingredient with antibacterial potential is bee bread, produced by the stingless bee species Heterotrigona itama. The aim of this study was to determine the antibacterial activity contained in Heterotrigona itama bee bread extract in fighting pathogenic bacteria. The test used the well method. The growth medium used was Mueller Hinton Agar (MHA) with a 24-hour incubation time. The concentrations used were 500, 250, and 125 µg/well. The percentage and inhibition zone of Heterotrigona itama bee bread extract varied among bacterial species. Based on the diameter of the inhibition zone at a concentration of 500 µg/well, inhibition of gram-positive bacteria tended to be greater than that of gram-negative bacteria. Bee bread produced by Heterotrigona itama bees has inhibitory activity against five types of pathogenic bacteria. The results also provide opportunities for further research, including the formulation and production of applicable products.